Irritable bowel syndrome: Factors of importance for disease‐specific quality of life. Issue 7 (13th July 2022) - Melchior, Chloé; Colomier, Esther; Trindade, Inês A.; Khadija, Mahrukh; Hreinsson, Jóhann P.; Törnblom, Hans; Simrén, Magnus
Abstract: Background: Irritable bowel syndrome patients report reduced disease‐specific quality of life (IBSQOL). Factors of potential relevance for QOL include gastrointestinal (GI), psychological, and somatic symptoms, demographics, and GI motor and sensory abnormalities. Objective: The aim of our study was to evaluate the relative importance of these factors on the different IBSQOL dimensions. Methods: We included irritable bowel syndrome (IBS) patients who completed validated questionnaires to assess QOL, stool form and frequency, GI symptom severity, psychological distress, GI‐specific anxiety, sense of coherence, and overall somatic symptom severity. Patients also underwent tests for oroanal transit time and rectal sensitivity. The nine dimensions of IBSQOL and their average (overall IBSQOL) were used as outcome variables, and factors associated with these were assessed using general linear models. Results: We included 314 IBS patients (74% female, mean age 36.3 ± 12.2 years). Higher stool frequency, GI and overall somatic symptom severity, psychological distress, and GI‐specific anxiety were independently associated with reduced overall IBSQOL, with the model explaining 60% of the variance ( p  < 0.001). In models using each of the nine dimensions as outcomes, different association of demographic factors, GI symptoms, overall somatic symptom severity, psychological factors and sense of coherence were associated with reduced IBSQOL, explaining 20%–60% of the variance, with GI‐specific anxiety being the factor that contributed most frequently. Rectal sensitivity or oroanal transit time were not independently associated with any of the dimensions. Conclusion: Different combinations of demographic factors, GI and somatic symptoms, and psychological factors are of importance for the nine IBSQOL dimensions. Gastrointestinal‐specific anxiety was the most important factor contributing to the majority of those dimensions in patients with IBS.